A CR1 polymorphism associated with constitutive erythrocyte CR1 levels affects binding to C4b but not C3b - Birmingham, Daniel J (Blackwell Science Inc, 2003)
The erythrocyte type one complement receptor (E-CR1) mediates erythrocyte binding of complement-opsonized immune complexes (IC), and helps protect against random deposition of circulating IC. Two linked CR1 polymorphisms occur in binding domains, at I643T and Q981H. In Caucasians, the variant alleles (643T, 981H) are associated with low constitutive E-CR1 expression levels. This study was conducted to determine if these polymorphisms affect ligand binding, and if so, represent risk factors for the autoimmune IC disease, systemic lupus erythematosus (SLE). In an ELISA comparing relative ligand binding differences, E-CR1 from individuals homozygous for the variant residues (643TT/981HH) exhibited greater binding to C4b, but not C3b, than homozygous wild-type E-CR1. Analysis of single-binding domain CR1 constructs demonstrated that the 981H residue imparted this enhanced C4b binding. No differences were observed in the 981H allele frequency between Caucasian controls (0·170, n = 100) and SLE patients (0·130, n = 150, P = 0·133), or between African American controls (0·169, n = 71) and SLE patients (0·157, n = 67). In a subset of individuals assessed for CR1 size, excluding from this analysis those expressing at least one B allele revealed a trend for over-representation of the 981H allele in Caucasian controls (0·231 frequency, n = 26) versus SLE patients (0·139, n = 83, P = 0·089), but again no difference between African American controls (0·188, n = 24) and SLE patients (0·191, n = 34). These data suggest that the 981H residue compensates for low constitutive expression of E-CR1 in Caucasians by enhancing C4b binding. This may contribute protection against SLE.